Endogenous opioidergic dysregulation of pain in fibromyalgia: a PET and fMRI study. Issue 10 (October 2016) - Schrepf, Andrew; Harper, Daniel E.; Harte, Steven E.; Wang, Heng; Ichesco, Eric; Hampson, Johnson P.; Zubieta, Jon-Kar; Clauw, Daniel J.; Harris, Richard E.
Abstract : Abstract: Endogenous opioid system dysfunction potentially contributes to chronic pain in fibromyalgia (FM), but it is unknown if this dysfunction is related to established neurobiological markers of hyperalgesia. We previously reported that µ-opioid receptor (MOR) availability was reduced in patients with FM as compared with healthy controls in several pain-processing brain regions. In the present study, we compared pain-evoked functional magnetic resonance imaging with endogenous MOR binding and clinical pain ratings in female opioid-naive patients with FM (n = 18) using whole-brain analyses and regions of interest from our previous research. Within antinociceptive brain regions, including the dorsolateral prefrontal cortex (r = 0.81, P < 0.001) and multiple regions of the anterior cingulate cortex (all r > 0.67; all P < 0.02), reduced MOR availability was associated with decreased pain-evoked neural activity. Additionally, reduced MOR availability was associated with lower brain activation in the nucleus accumbens (r = 0.47, P = 0.050). In many of these regions, pain-evoked activity and MOR binding potential were also associated with lower clinical affective pain ratings. These findings are the first to link endogenous opioid system tone to regional pain-evoked brain activity in a clinical pain population. Our data suggest that dysregulation of the endogenous opioid system in FM could lead to less excitation in antinociceptive brain regions by incoming noxious stimulation, resulting in the hyperalgesia and allodynia commonly observed in this population. We propose a conceptual model of affective pain dysregulation in FM. Abstract : Supplemental Digital Content is Available in the Text.The μ-opioid receptor system is intricately linked to brain responses to pain in fibromyalgia. Patients with fibromyalgia may be less responsive to endogenous and other opioids.